Pengembangan Video Pembelajaran Berbasis Think Talk Write (TTW) Pada Kemampuan Menulis Siswa Sekolah Dasar - Sepwinsyah Putra; Abdul Muktadir; Endang Widi Winarni (Universitas Bengkulu, 2022)
The research aims to develop Think Talk write (TTW) based learning videos with writing skills materials for V-grade students that can be used to improve student learning outcomes. Researchers developed TTW-based learning videos using Research and Development research methods, the development of TTW-based learning videos uses 3-D models that define, design, and develop. The feasibility of TTW-based learning videos was validated by 6 experts with an average validation score of 0.88 with material expert details worth 0.91, linguists worth 0.91 and media experts valued at 0.84. with an average based on the interpretation table aiken V validation is in the high category. The teacher's response based on the interview showed a positive response in the